Fermentation of 1,2-Propanediol and 1,2-Ethanediol by Some Genera of Enterobacteriaceae, Involving Coenzyme B(12)-Dependent Diol Dehydratase - Toraya, Tetsuo (1979)
Klebsiella pneumoniae (Aerobacter aerogenes) ATCC 8724 was able to grow anaerobically on 1,2-propanediol and 1,2-ethanediol as carbon and energy sources. Whole cells of the bacterium grown anaerobically on 1,2-propanediol or on glycerol catalyzed conversion of 1,2-diols and aldehydes to the corresponding acids and alcohols. Glucose-grown cells also converted aldehydes, but not 1,2-diols, to acids and alcohols. The presence of activities of coenzyme B(12)-dependent diol dehydratase, alcohol dehydrogenase, coenzyme-A-dependent aldehyde dehydrogenase, phosphotransacetylase, and acetate kinase was demonstrated with crude extracts of 1,2-propanediol-grown cells. The dependence of the levels of these enzymes on growth substrates, together with cofactor requirements in in vitro conversion of these substrates, indicates that 1,2-diols are fermented to the corresponding acids and alcohols via aldehydes, acyl-coenzyme A, and acyl phosphates. This metabolic pathway for 1,2-diol fermentation was also suggested in some other genera of Enterobacteriaceae which were able to grow anaerobically on 1,2-propanediol. When the bacteria were cultivated in a 1,2-propanediol medium not supplemented with cobalt ion, the coenzyme B(12)-dependent conversion of 1,2-diols to aldehydes was the rate-limiting step in this fermentation. This was because the intracellular concentration of coenzyme B(12) was very low in the cells grown in cobalt-deficient medium, since the apoprotein of diol dehydratase was markedly induced in the cells grown in the 1,2-propanediol medium. Better cell yields were obtained when the bacteria were grown anaerobically on 1,2-propanediol. Evidence is presented that aerobically grown cells have a different metabolic pathway for utilizing 1,2-propanediol.